PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION DENGAN BANTUAN MEDIA INTERAKTIF ANIMASI TERHADAP HASIL BELAJAR PPKn SISWA KELAS V UPTD.SD INPRES LASIANA KOTA KUPANG - Debora Natonis; Petrus Ly; Martha K. Kota (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Debora Natonis NIM.2101140052 with the tittle “ The Effect of Group InvestigationLearning Model with the help of Interactive Animation Media on the LearningOutcomes of PPKn Class V Students of UPTD. SD Inpres Lasiana Kupang City”.The problem in this study is to examine the significant effect of the GroupInvestigation learning outcomes of PPKn Class V Students of UPTD.SD InpresLasiana Kupang City, with the aim of improving students learning outcomes inPancasila education learning about My Indonesian Regional Culture. This studyuses the Pre-Experimental Design research type with a quantitative approach tothe One Group Pretest Posttest research design. The population in this study were28 class V C students of UPTD. SD Inpres Lasiana, Kupang City. The samplingtechnique used was a saturated sample where all populations were used assamples. Data collection techniques and instruments were observation sheets andtest instruments. The research instrument was a test in the form of a prestest andposttest to measure learning outcomes. The question instrument before beingused, was first used for validity and reliability testing. After the data was collected,it was analysed and used for hypothesis testing.This research was conducted atUPTD. SD Inpres Lasiana Kupang City Class V C. Furthermore, the results of thehypothesis testing, using paired samples t-test showed that the significance value(2-tailed) was 0,000. This shows that at the significamce level (2-tailed) < 0,05. Inaccordance with the basis for decision making, this is because the sig. (2-tailed)value < 0,05, so there is a significant difference between the learning outcomes inthe Pretest-Posttest data. Based on the results of the study above, it can beconcluded that there is an influence between the Group Investigation learningmodel with the help of interactive animation media on the PPKn learning outcomesof class V students of UPTD. SD Inpres Lasiana, Kupang City.